Use of small intestinal submucosa for corporal body grafting in cases of epispadias and epispadias/exstrophy complex. Issue 4 (August 2019) - Ballesteros, N.; Moscardi, P.R.M.; Blachman-Braun, R.; Salvitti, M.; Alam, A.; Castellan, M.; Kozakowski, K.; Gosalbez, R.; Labbie, A.
Summary: Background: Male epispadias is a rare congenital urogenital anomaly in which the meatus is ectopically located along the dorsal midline of the penile shaft. In cases associated with severe curvature, functional and cosmetic outcomes could be accomplished by lengthening the shorter dorsal surface with the use of corporal grafting. Various graft materials have been used in the past for hypospadias repair including tunica vaginalis, dermis, and small intestinal submucosa (SIS). The use of SIS grafting for corporoplasty during epispadias repair has rarely been described in the literature. Objective: To report the experience in the management of dorsal corporal body grafting using SIS in children with severe penile curvature due to epispadias. Study design: The authors retrospectively reviewed the charts of all patients with epispadias or bladder exstrophy/epispadias complex and severe dorsal chordee (>40°) who underwent epispadias repair with single-layer SIS for corporal body grafting. Clinical variables, surgical technique, and outcomes were analyzed. Results: A total of nine consecutive patients underwent staged epispadias repair with dorsal corporal single-layer SIS grafting (summary figure). Of these, four (44.4%) had primary penopubic epispadias, one (11.1%) had mid-shaft epispadias, and four (44.4%) had bladder exstrophy/epispadias complex. The mean age at surgery was 13.4 ± 6 months. After phalloplasty with SIS grafting, there were no reported complications related to the graft during the post-operative period or follow-up visits. Discussion: Although traditional techniques for epispadias repair allow some degree of corporal lengthening, they also result in abrupt medial rotation of the corporal bodies leading to torqueing and potential unsatisfactory cosmetic results. In contrast, the authors use single-layer SIS for corporal body grafting, and this study technique results in a more gradual inward rotation thus allowing more anatomical accuracy. Furthermore, an advantage of the use of SIS over other grafting materials is that there is no need to harvest an autologous graft such as tunica vaginalis or dermis. Conclusion: Epispadias repair using single-layer SIS corporal body grafting is an effective, safe, and feasible method, which provides satisfactory cosmesis and correction of dorsal curvature in congenital epispadias in children. Furthermore, a more normal penis appearance, without a decrease in the corporal length or diameter, is achieved with this technique.